Philosophical analysis of the phenomena arising among the Kazakh youth - Dussipova, A.S.; Peeter, M. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
This article presents a philosophical analysis of the phenomena arising among the modern youth of Kazakhstan. The research is based on an integrated approach that combines comparative analysis and empirical research aimed at a multifaceted consideration of the problem. The authors seek to identify the causes of existing problems. Through a literary review, the authors examine scientific papers, articles and other publications, including both domestic and international sources, in order to get the most objective picture of the current state of the problem. The comparative analysis allows the authors to assess the situation of young people in Kazakhstan in the context of global trends, identifying unique and common challenges and opportunities. A survey was conducted in order to obtain primary data directly from young people for an in-depth analysis of their views, attitudes, life values and ideas about the future. The authors cover key topics such as spiritual emptiness, the search for meaning, spiritual adaptation and growth. In conclusion, the authors present a model of an integrated approach to solving modern phenomena among young people. This model is an integration of acquired knowledge and proposals developed on the basis of in-depth analysis and extensive research. The article promotes a deeper understanding of the spiritual, cultural and social problems faced by young people and offers constructive solutions to support their development and well-being in the face of modern problems.
Қазақстандық жастарда туындайтын құбылыстарды философиялық талдау
Философский анализ явлений, возникающих у казахстанской молодежи
Keywords: youth; spiritual emptiness; search for meaning; spiritual adaptation; cultural identity; globalization; sociocultural challenges; cultural characteristics; social behavior; personal development